NEPOTISM, CRONYISM, AND ORGANIZATIONAL COMMITMENT AMONG RESCUE WORKERS: EXAMINING ORGANIZATIONAL ALIENATION AS A MEDIATOR (Contemporary Journal of Social Science Review, 2025)
Rescue work is a very demanding occupation that bears high organizational commitment because it is risk-prone, teamwork-dependent, and directly affects the community through safety provision. Nonetheless, some undesirable organizational practices like nepotism and cronyism can undermine the psychological attachment of employees to their organization. In the current research, the association between nepotism, cronyism, and organizational commitment was investigated among rescue workers, and the association of organizational alienation as an intermediate factor examined. A quantitative correlational research design was adopted, whereby a sample of N = 400 rescue workers working with Rescue 1122 in Pakistan was sampled with the help of convenience sampling. The sample consisted of emergency responders, ambulance workers, and disaster management personnel who had at least one year of job experience. The administration included standardized self-report measures such as the Nepotism Scale, Organizational Cronyism Scale, Work Alienation Scale, and Organizational Commitment Scale. Data were analyzed with Pearson product-moment correlation and covariance-based structural equation modeling (CB-SEM). The results indicated strong negative associations between nepotism, cronyism and organizational commitment. Nepotism and cronyism were also found to be significant positive predictors of organizational alienation, as well as negative predictors of organizational commitment. The mediation analysis also revealed that organizational alienation significantly mediated the relationship of nepotism and cronyism with organization commitment in a partial manner. These results indicate that favoritism in rescue organizations strains a sense of alienation, which ultimately erodes the level of commitment of employees to their organization. The study shows that organizational practices that are transparent, just, and based on merit are significant in emergency service institutions to minimize alienation, promote commitment, and elevate overall organizational effectiveness and provision of services.